Molecular Serotyping and Antibiotic Resistance Patterns of Escherichia coli Isolated in Hospital Catering Service in Morocco - Benjelloun Touimi Ghita; Laila Bennani; Sanae Berrada; Moussa Benboubker; Bahia Bennani (International Journal of Microbiology)
Escherichia coli is related to foodborne disease and outbreaks worldwide. It mainly affects persons at high risk as newborns, infants, and individuals with impaired immune system in hospitals. Multidrug-resistant E. coli is currently spreading both in community and hospital settings. Our study aims to evaluate the presence of E. coli and the incidence of its antibiotic resistance in samples obtained from various cooked and raw foods (N = 300), food contact surfaces (N = 238), and food handlers (N = 40) in Moroccan hospital catering service. E. coli was identified using API 20E, and the antibiotic resistance patterns were obtained using the agar disk diffusion methods. However, PCR method was used for O157 and H7 typing. The samples analysis showed that 14.33%, 24.16%, and 45% of food, surfaces, and food handlers harbored E. coli, respectively, with the highest rates obtained in raw meats (34.88%) and salads (34.88%). Molecular amplification shows that 14 E. coli isolates carried the flagellar antigen H7, while there are no isolates showing amplification for O157. The high rate of resistance was noted against ampicillin (100%), amoxicillin-clavulanate acid (100%), nalidixic acid (61.62%), and cefotaxime (59.49%), and isolates obtained from food handler’s hands showed the highest rates of resistance. None of the isolates are extended-spectrum beta-lactamases producing, while 27.7% of the isolates were metallo-beta-lactams producing. This first study conducted on Moroccan hospital catering services may draw the authorities’ attention to the necessity of setting up a surveillance system to monitor the food preparation process and the safety of prepared food in healthcare settings.